Cathepsin S Deficiency Mitigated Chronic Stress–Related Neointimal Hyperplasia in Mice. Issue 14 (16th July 2019) - Wang, Hailong; Meng, Xiangkun; Piao, Limei; Inoue, Aiko; Xu, Wenhu; Yu, Chenglin; Nakamura, Kae; Hu, Lina; Sasaki, Takeshi; Wu, Hongxian; Unno, Kazumasa; Umegaki, Hiroyuki; et al.
Abstract : Background: Exposure to chronic psychosocial stress is a risk factor for atherosclerosis‐based cardiovascular disease. We previously demonstrated the increased expressions of cathepsin S (CatS) in atherosclerotic lesions. Whether CatS participates directly in stress‐related neointimal hyperplasia has been unknown. Methods and Results: Male wild‐type and CatS‐deficient mice that underwent carotid ligation injury were subjected to chronic immobilization stress for morphological and biochemical studies at specific times. On day 14 after stress/surgery, stress enhanced the neointima formation. At the early time points, the stressed mice had increased plaque elastin disruption, cell proliferation, macrophage accumulation, mRNA and/or protein levels of vascular cell adhesion molecule‐1, angiotensin II type 1 receptor, monocyte chemoattractant protein‐1, gp91 phox, stromal cell–derived factor‐1, C‐X‐C chemokine receptor‐4, toll‐like receptor‐2, toll‐like receptor‐4, SC35, galectin‐3, and CatS as well as targeted intracellular proliferating‐related molecules (mammalian target of rapamycin, phosphorylated protein kinase B, and p‐glycogen synthase kinase‐3α/β). Stress also increased the plaque matrix metalloproteinase‐9 and matrix metalloproteinase‐2 mRNA expressions and activities and aorta‐derived smooth muscle cell migration and proliferation. The genetic or pharmacological inhibition of CatS by its specific inhibitor (Z‐FL‐COCHO) ameliorated the stressed arterial targeted molecular and morphological changes and stressed aorta‐derived smooth muscle cell migration. Both the genetic and pharmacological interventions had no effect on increased blood pressure in stressed mice. Conclusions: These results demonstrate an essential role of CatS in chronic stress–related neointimal hyperplasia in response to injury, possibly via the reduction of toll‐like receptor‐2/toll‐like receptor‐4–mediated inflammation, immune action, and smooth muscle cell proliferation, suggesting that CatS will be a novel therapeutic target for stress‐related atherosclerosis‐based cardiovascular disease.